2017
DOI: 10.1186/s12957-016-1085-0
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of upper cervical spine metastases: a retrospective study of 39 cases

Abstract: BackgroundThe surgical treatment of upper cervical spine metastases are controversial up to now. By summarizing and analyzing the clinical data of the upper cervical spine involved metastases treated surgically in our center, we mainly aimed to investigate the surgical decisions and outcomes so as to provide more references for the clinical treatment of this special and complex spine metastasis.MethodsWe evaluated the patients’ pre- and post-operative neck pain and neurologic function with paired t test, follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 38 publications
(94 reference statements)
2
22
1
Order By: Relevance
“…4,5,[26][27][28][29] Currently, a multidisciplinary approach is the most common treatment strategy for spine metastases, which usually includes surgery, [29][30][31][32][33][34][35][36] radiotherapy, 15,[37][38][39][40][41][42][43][44][45][46][47][48] bone cement, 49,50 bisphosphonates 51 and chemotherapy. 51 Radiotherapy is an efficient therapeutic approach for symptomatic spine metastases patients that has a low morbidity rate. 41,[52][53][54][55][56] Surgery remains the standard treatment for patients with rapidly progressive spinal cord compression or patients with a high risk of fracture, but it can cause postoperative complications and delay the initiation of other anticancer therapies.…”
Section: Treatment Evolution Of Spine Metastasesmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5,[26][27][28][29] Currently, a multidisciplinary approach is the most common treatment strategy for spine metastases, which usually includes surgery, [29][30][31][32][33][34][35][36] radiotherapy, 15,[37][38][39][40][41][42][43][44][45][46][47][48] bone cement, 49,50 bisphosphonates 51 and chemotherapy. 51 Radiotherapy is an efficient therapeutic approach for symptomatic spine metastases patients that has a low morbidity rate. 41,[52][53][54][55][56] Surgery remains the standard treatment for patients with rapidly progressive spinal cord compression or patients with a high risk of fracture, but it can cause postoperative complications and delay the initiation of other anticancer therapies.…”
Section: Treatment Evolution Of Spine Metastasesmentioning
confidence: 99%
“…Longsegment percutaneous screw fixation could provide stability and improve quality of life in spine metastases patients who had early radiation therapy. Yang 2017 51 Surgery and chemotherapy Surgery for upper cervical spine metastases patients was an effective treatment with low mortality. Surgery combined with an adjuvant therapy could relieve the regional pain and enhance the neurological function, improve the quality of life and prolong the survival period in atlantoaxial metastases patients.…”
Section: Author and Yearmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, plate osteosynthesis is also possible and in 2016 Janssen et al showed that it is not the type of osteosynthesis performed in the region of the humerus diaphysis that primarily affects the outcome but rather tumour status based on the Bauer score [28]. Yang et al (2011) recorded a higher MST (MST: Musculoskeletal Tumor Society) score for intramedullary nailing than for prosthetic implant treatment [29]. In 2009, Gruber et al recommended intralesional curettage of metastases in a population in 19 patients with humeral metastases in combination with cement filling and intramedullary nailing and/or plate fixation due to the shorter surgery times, shorter hospital stays and fewer complications [30].…”
Section: Fracture Stabilisation and Pain Reduction In Patients With Amentioning
confidence: 99%
“…1 Metastatic involvement of the atlanto-occipital junction is rare 2 with only 16 cases previously reported ( Table 1). [3][4][5][6][7][8][9][10] Specifically, the most frequent primary tumour was lung cancer in six cases, following by thyroid cancer in three patients.…”
mentioning
confidence: 99%